2015
DOI: 10.3109/13561820.2015.1075474
|View full text |Cite
|
Sign up to set email alerts
|

The National United States Center Data Repository: Core essential interprofessional practice & education data enabling triple aim analytics

Abstract: Understanding the impact that interprofessional education and collaborative practice (IPECP) might have on triple aim patient outcomes is of high interest to health care providers, educators, administrators, and policy makers. Before the work undertaken by the National Center for Interprofessional Practice and Education at the University of Minnesota, no standard mechanism to acquire and report outcome data related to interprofessional education and collaborative practice and its effect on triple aim outcomes … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 9 publications
(18 reference statements)
0
3
0
Order By: Relevance
“…In the original article about the “Triple Aim,” the authors suggested that “physician-centric care” was a barrier to meeting these pursuits [ 5 ]. Interprofessional collaborative practice has been endorsed as an important transition in health care delivery that will further the “Triple Aim” by encouraging teamwork among health care providers [ 6 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…In the original article about the “Triple Aim,” the authors suggested that “physician-centric care” was a barrier to meeting these pursuits [ 5 ]. Interprofessional collaborative practice has been endorsed as an important transition in health care delivery that will further the “Triple Aim” by encouraging teamwork among health care providers [ 6 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…The lack of appropriate assessments and tools to measure the effects of interprofessional education on collaborative practice, and the effects of collaborative practice on cost, quality, and patient experience outcomes, is well reported in the literature (e.g. Committee on Measuring, 2015; Pechacek et al, 2015;Reeves, 2016). There have been multiple calls to move the field forward.…”
Section: Evolution In Center Philosophymentioning
confidence: 99%
“…Since its inception, the measurement of team function in practice and interprofessional education has risen to an even higher priority. The National Center's experience with the National Innovations Network and building the National Center Data Repository (Pechacek et al, 2015) identified an especially acute need to find good measures of "teamwork," as experienced by different kinds of groups working in various education and clinical environments. As a result, the National Center has supported the development of the Assessment of Clinical Environment (ACE-15) tool (Tilden, Eckstrom, & Dieckmann, 2015) and other instruments used in real time in the Nexus Innovations Network.…”
Section: The National Center's Missionmentioning
confidence: 99%